Relationship of Respondent’s Characteristic with The Risk of Diabetes Mellitus and Dislipidemia at Tanah Kalikedinding - Nina Widyasari (Jurnal Berkala Epidemiologi, 2017)
Non-communicable disease (NCD) is one of the world's health problems including Indonesia. Some types of NCD that are found are dyslipidemia and diabetes mellitus (DM). This study aims to describe the relationship of age, sex, and education with DM and dyslipidemia in the Tanah Kalikedinding Sub-district, Surabaya. This study is a cross-sectional study design. The population in this study were all residents living in the 5th neighborhood, 2th Hamlet, Tanah Kalikedinding Sub-district, Kenjeran District with a population of 402 people. Samples were taken by simple random sampling with the Slovin formula amounted to 50 people. The independent variables studied were age, sex, and education level, while the dependent variables in this study were DM status and dyslipidemia status. Data analysis using frequency distribution tables and Chi-square test. The results of this study indicate that there is a relationship between the age of the respondent (p = 0.005), sex (p = 0,000), and education (p = 0.001) with the incidence of diabetes mellitus with the risk of dyslipidemia. Health workers and related cross-sector are advised to provide education to Kalikedinding land residents regarding the importance of implementing healthy lifestyles by undergoing regular control of eating habits, exercise, and blood sugar checks, and dyslipidemia. The government also needs to support the program that is currently being developed, namely the NCD-Integrated Health Care Post (Posbindu).